Pandangan Mufassir tentang Surga (Tempat) Nabi Adam: (Studi al-Tafsịr al-Munịr, Majma’ al-Bayān fi Tafsịr al-Qur’ān, dan Amālị al-Murtaḍā) - Saadatus Salamah; Muksi, Mohammad (IAIN Madura, 2024)
Scholars or commentators have differed in opinion about the paradise that Prophet Adam once inhabited particularly because the word al-jannah has various meanings. Some say that the heaven of Prophet Adam is in the sky, while others assume it on the earth. The difference is partly because the word al-hubūt has also various meanings. This research relied on literature search using descriptive analysis which aims to get a complete and clear picture of the problem, namely the story of Adam's ‘eviction’ from heaven in the Qur'an according to exegesis of Wahbah al-Zuhailị, al-Tābarsị and al-Syarịf al-Murtaḍā in al-Tafsịr al-Munịr, Majma’ al Bayān fị Tafsịr al - Qur’ān and Amālị al – Murtaḍā respectively. The result of this study is that three commentators differed in the opinion about the heaven. Wahbah al-Zuhailị preferred that Adam's heaven in the sky, while al-Tābarsị and al-Syarịf al-Murtaḍā said that Adam's heaven is on earth. Meanwhile, Wahbah al-Zuhailị interprets al-hubūt as